The casual association between mTOR-related proteins and rheumatoid arthritis: Mendelian randomization in European populations - Zhoujun Yuan; Jiayi L; Rong Zhao; Heyi Zhang; Shengxiao Zhang (Open Exploration Publishing Inc., 2024)
Aim: Rheumatoid arthritis (RA) is an autoimmune disorder marked by an overgrowth of joint tissue and inflammation of the synovium. The mammalian target of rapamycin (mTOR), functioning as a serine/threonine protein kinase, is recognized for its role in controlling cell proliferation, metabolism, and inflammatory responses. While there is some evidence hinting at a link between RA and proteins downstream of mTOR, the findings are not definitive. In light of this, we have undertaken a Mendelian randomization (MR) analysis to investigate the potential connection between mTOR and RA. Methods: A two-sample MR study was performed by utilizing significant single nucleotide polymorphisms (SNPs) derived from a comprehensive genome-wide association study (GWAS) dataset, which included 58,284 samples of RA and 3,301 samples of mTOR-related proteins, as instrumental variables (IVs). The primary MR analysis techniques employed were inverse variance weighted (IVW), weighted median (WM), and MR-Egger regression. Additionally, sensitivity analyses were carried out on the IVs to evaluate heterogeneity and pleiotropy using MR-Egger, leave-one-out, and MR pleiotropy residual sum and outlier (MR-PRESSO) methods. Furthermore, to validate the robustness of the findings, replication analyses were also conducted using another RA GWAS dataset focusing on European populations. Results: The main findings indicated that there is no causal link between mTOR-related proteins and RA. The genetically elevated levels of mTOR-related proteins do not appear to raise the risk of RA [AKT (p = 0.721), ATF6 (p = 0.369), ATG7 (p = 0.112), BECN1 (p = 0.599), EIF4A3 (p = 0.652), EIF4B (p = 0.989)]. Additionally, the Cochran's Q test did not detect any heterogeneity across all proteins. The MR-PRESSO analysis also found no evidence of pleiotropy. The replication cohort confirmed these results, showing once more that there is no connection between mTOR and RA, which suggests that the initial findings are both robust and reliable. Conclusions: Although earlier research has hinted at a possible link between mTOR pathway proteins and RA, our study does not endorse a causal relationship between the two. Additional studies are required to clarify the intricate mechanisms that drive RA and to determine the role of mTOR signaling in the disease process.